GOOD GOVERNANCE MANAGEMENT OF FACTORS AFFECTING THE ACHIEVEMENT MOTIVATION, OFFICE OF THE VOCATIONAL EDUCATION COMMISSION, NONTHABURI - Thamthong, Wiroon; Chaisuwan, Saruda (Journal of Educational Review Faculty of Education in MCU, 2022)
The objective of this research article to 1) Study the administration according to the principles of good governance of educational institutions. Under the Office of the Private Vocational Education Commission Nonthaburi. 2) Study the teacher's achievement motivation. Under the Office of the Private Vocational Education Commission Nonthaburi. and 3) A study of good governance that affects teachers' achievement motivation. The sample group consisted of 180 teachers at Under the Office of the Private Vocational Education Commission Nonthaburi. by Simple random sampling. Research instrument was 5 rating scale with IOC between 0.67 - 1.00 and the reliability at 0.988 was used to collect data. The statistics used to analyze descriptive statistical data were percentage, mean, and standard deviation, the inferential statistics was multiple regression by Stepwise method. The results of this study provided that 1) Administration according to the principles of good governance of educational institutions relationship at a statistically significant level of .01 at a high level, 2) Teacher Achievement Motivation relationship at a statistically significant level of .01 at a high level, and 3) Management according to the principles of good governance affecting teacher achievement motivation Under the Office of the Private Vocational Education Commission Nonthaburi found that rule of law and the main aspect focuses on consensus affecting teacher achievement motivation. The correlation coefficient (R) was at 0.753 which implies that the Variances in Teacher Achievement Motivation about 54.10 percent (R2 = 0.541). The standard scores (β) for teaching tasks and listening abilities were 1.701, and 0.819, respectively.